Analysis of application effect of 220 kV UPFC demonstration project in Shanghai grid. Issue 16 (25th October 2018) - Cui, Yong; Yu, Yinghui; Bao, Wei; Feng, Yuyao; Guo, Qiang; Xie, Wei; Jin, Minjie
Abstract : The feasibility study of unified power flow controller (UPFC) application in 220 kV Shanghai Grid is conducted based on the analysis of the practical operation of the grid. The location selection method and scheme are proposed for the application of 220 kV UPFC demonstration project. The application effect of the demonstration project of UPFC is evaluated from various perspectives including enhancement of interface transfer capability, improvement of voltage stability performance of the grid and contribution to balancing of reactive power in 220 kV sectionalised systems.